Heuristic Learning and Sport: Theoretical Lines and Operational Proposals - Tiziana D'Isanto; Gaetano Altavilla; Giovanni Esposito; Francesca D'Elia; Gaetano Raiola (University of Bologna, 2022)
This study aims to open a critical scenario on the current paradigm of reference for teaching sports techniques by pointing to a methodological perspective that is more in keeping with the theoretical reference framework of the ecological-dynamic approach. Currently, the Constraints-led Approach is considered very useful for teaching sports techniques; however, the transition from pure theory to practice is not so simple and consistent with the heuristic learning paradigm. The purpose is to highlight, starting from the theoretical lines, the methodological applications of the different ways of applying the reference paradigm, analyzing the contrasts of the significant aspects and the uniqueness and unrepeatability of heuristic learning. For this purpose, an in-depth review of the scientific literature was conducted, highlighting the main critical points of the approach, also defined as nonlinear, with the consequent elaboration of operational proposals for the various macro-families of sports.